(3TQM ebUhQI GHf OQjO GdUZQis - (3jMji Hf Ydj Hf GdMSf Hf ehSi Hf HSWGe GdNWjH GdJHQjRj GddZhj , CHh RcQjG , J (B502 (3g` s; (3GHf OQjO , CHh HcQ eMeO Hf GdMSf Hf OQjO GdCROj, GHf OQjO,J (B321 (3g` s
(3ChdgG (B:s
(3dCJQcff Edi Gdghi (Bxxx (3hGMPQ eaGQbI GdghGA s
(3BNQgG (B:s
(3hCMdd ef GdRGe GdQHi (Bxxx (3Ef cfJ ef Ggd GdQHGA hbY GdaQGZ ef fSN s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3GfXQ GdLRA Gdhd Qbe (B568 (3COHs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs